2011
DOI: 10.1080/07347332.2010.548442
|View full text |Cite
|
Sign up to set email alerts
|

A Private Caregiver ListServ: Maximum Benefit for Minimum Cost

Abstract: A private ListServ was created as a psychosocial intervention for the caregivers of the brain tumor patients in a large metropolitan cancer center. Caring for someone with a brain tumor can be quite challenging, and the day-to-day responsibilities restrict the amount of discretionary time allotted the caregiver. Consequently, they can become isolated and overwhelmed. It was conceived that, for convenience sake, a ListServ might be the solution to best serve this population. The hope being that sharing with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…[7][8][9][10][11] Listserv communication has been used in different ways within the health care system, including caregiver support, peer support for individuals with various diseases, and as an information-sharing tool for health care professionals. [8][9][10]12,13 The latter have used listservs for networking, for sharing resources, and for accessing the expert opinions of colleagues. 11 Research has shown that listservs for health care professionals are valuable resources that aid in the preparation of educational presentations, that alter policies or documentation, and that help shape practices or systems.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Listserv communication has been used in different ways within the health care system, including caregiver support, peer support for individuals with various diseases, and as an information-sharing tool for health care professionals. [8][9][10]12,13 The latter have used listservs for networking, for sharing resources, and for accessing the expert opinions of colleagues. 11 Research has shown that listservs for health care professionals are valuable resources that aid in the preparation of educational presentations, that alter policies or documentation, and that help shape practices or systems.…”
mentioning
confidence: 99%
“…Themes of discussion were similar to data generated from descriptive qualitative studies and included cognitive problems in the care recipient, practical issues and caregiver burden. Lucas et al [26] reviewed an on-line support group for caregivers of persons with a PMBT. They reported that at three years after implementation, on-line exchanges became more regular and thoughtful and were one of the only studies to include a discussion of the cost of the intervention.…”
Section: • • Intervention Preparation Studiesmentioning
confidence: 99%
“…Data from intervention studies highlight additional issues for future work. Lucas [26] described the cost of implementing and maintaining an online support group; future intervention studies should include a cost analysis to inform translation into clinical practice. Findings from Keir's [45] work emphasize that although caregivers are distressed, they may not take advantage of opportunities to relieve that stress.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…The collective nature of this message distribution can instill a sense of community, to the point that listservs have been invoked as a means of psychosocial intervention to help cancer patients and their caregivers lessen their isolation through contact with their peers 8,9 .…”
Section: Pastmentioning
confidence: 99%